2017
DOI: 10.3390/fermentation3040056
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic and Life Cycle Assessment of Wastewater Management from Potato Starch Production: Present Status and Alternative Biotreatments

Abstract: Potato liquor, a byproduct of potato starch production, is steam-treated to produce protein isolate. The heat treated potato liquor (HTPL), containing significant amounts of organic compounds, still needs to be further treated before it is discarded. Presently, the most common strategy for HTPL management is concentrating it via evaporation before using it as a fertilizer. In this study, this scenario was compared with two biotreatments: (1) fermentation using filamentous fungus R. oryzae to produce a protein-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Some studies proposed pathways towards enhanced nutrient bioavailability [10,[58][59][60] and improved human health/well-being [61][62][63][64] (including microbiome therapies [63][64][65][66]), advances of interest to contrast the adverse effects of some negative externalities. Furthermore, the design of several works looking at reducing resource dissipation, saving energy [52,69], valorising foods by-products [52,70,71], foods wastes [72][73][74], and wastewater [75][76][77]. Finally, some strategies can preserve microbial diversity associated with food fermentation [78][79][80].…”
Section: Tailored Food Fermentative Processes To Reduce Negative Exte...mentioning
confidence: 99%
“…Some studies proposed pathways towards enhanced nutrient bioavailability [10,[58][59][60] and improved human health/well-being [61][62][63][64] (including microbiome therapies [63][64][65][66]), advances of interest to contrast the adverse effects of some negative externalities. Furthermore, the design of several works looking at reducing resource dissipation, saving energy [52,69], valorising foods by-products [52,70,71], foods wastes [72][73][74], and wastewater [75][76][77]. Finally, some strategies can preserve microbial diversity associated with food fermentation [78][79][80].…”
Section: Tailored Food Fermentative Processes To Reduce Negative Exte...mentioning
confidence: 99%
“…They reported that although the integrated process imposed greater capital costs than only fungal cultivation on stillage, it could result in up to 48% increase in the net present value (NPV). In another work, Souza Filho et al [41] performed a technical and economical evaluation, and a life cycle assessment (LCA) on the production of filamentous fungal biomass from potato liquor, a by-product of potato starch production. This research focused on different treatment scenarios for heat-treated potato liquor, with one including the application of final fungal biomass as a fish feed supplement.…”
Section: Filamentous Fungi Cultivationmentioning
confidence: 99%
“…In current practices, residual effluents from the potato starch industry usually end up as fertilizer [5]. This common Highlights • Fungal cultivation effluent is a potential feedstock for VFA production.…”
Section: Introductionmentioning
confidence: 99%
“…scenario has been compared with other scenarios in different literatures [5] and the use of PPL for the cultivation of fungal biomass and proteins [6,7], yeast biomass [8], and enzyme production [9] was investigated. PPL has been valorized through conversion of a high fraction of its nutrients into food and feed grade fungal biomass in a previous study [7].…”
Section: Introductionmentioning
confidence: 99%